Przykłady zapożyczeń z języka polskiego w wybranych ukraińskich powieściach historycznych pisarzy galicyjskich - Krzywicka-Ustrzycka, Anna (Acta Polono-Ruthenica, 2008)
The analysis of research material aims to present the borrowings from the Polish language employed in two selected historical novels by 20th century writers from Galitia. The examples of borrowings subject to the description and analysis prove that Polish and Ukrainian languages exerted linguistic influence on each other through common history and culture of Eastern Galitia. The analysis of borrowings accounts for the introduction to further studies of borrowings as used by other writersfrom Galitia, which would enable to address issues of linguistic specificity of particular region in terms of borrowings.